Preparation method of bamboo charcoal / regenerated cellulose composite fiber

Through the in-situ polymerization method of polydopamine and polysiloxane quaternary ammonium salts, the problems of dispersion and interface interaction of bamboo charcoal fibers under high addition amounts were solved, and the antibacterial and mechanical properties of bamboo charcoal/regenerated cellulose composite fibers were significantly improved. .

CN119162679AActive Publication Date: 2024-12-20SICHUAN UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411366518.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform and stable dispersion and interface interaction of bamboo charcoal fibers in polymer matrix under high bamboo charcoal additive amount, resulting in poor mechanical properties and functional properties of bamboo charcoal fibers.

Method used

The surface in situ polymerization method of polydopamine and polysiloxane quaternary ammonium salt is adopted. The surface of bamboo charcoal is modified by dopamine and combined with nanoparticles to increase the active site, and the grafting efficiency of bamboo charcoal and polysiloxane quaternary ammonium salt is improved to form Modified bamboo charcoal dispersion and spinning with regenerated cellulose fibers to achieve high density modification and interface enhancement.

Benefits of technology

It significantly improves the antibacterial and mechanical properties of bamboo charcoal/regenerated cellulose composite fiber, enhances the dispersion and interface compatibility of the fiber, and improves the overall performance of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162679A_ABST
    Figure CN119162679A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of bamboo charcoal / regenerated cellulose composite fibers. The preparation method comprises the following steps: S1, obtaining bamboo charcoal particles; s2, dispersing bamboo charcoal, and adding dopamine, tris (hydroxymethyl) aminomethane and functional nanoparticles to obtain a polydopamine modified bamboo charcoal dispersion liquid; s3, polysiloxane quaternary ammonium salt is added, and modified bamboo charcoal is obtained; s4, mixing the modified bamboo charcoal, cellulose and an organic solvent to obtain a modified bamboo charcoal regenerated cellulose fiber spinning solution; and S5, carrying out wet spinning to obtain the modified bamboo charcoal / regenerated cellulose composite fiber. The density of active groups on the surfaces of bamboo charcoal particles is improved by adopting polydopamine, meanwhile, the number of active sites is increased by utilizing the modification effect of the polydopamine and firm combination of the polydopamine and nano particles, the grafting efficiency of the bamboo charcoal and polysiloxane quaternary ammonium salt is improved, interaction between the bamboo charcoal and a matrix and dispersity in the matrix are achieved, and the bamboo charcoal / polysiloxane quaternary ammonium salt composite material is prepared. Therefore, the prepared modified bamboo charcoal / regenerated cellulose composite fiber has excellent antibacterial property and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a method for preparing bamboo charcoal / regenerated cellulose composite fibers. Background Art

[0002] Bamboo charcoal fiber is a new type of functional fiber developed by combining bamboo charcoal with textile fiber. It has the characteristics of adsorption, antibacterial and antibacterial, far infrared, negative ions, heat storage, moisture absorption and breathability, and green environmental protection. At present, bamboo charcoal fiber has important application prospects in clothing, home textiles, medical protective clothing, military aerospace operator protective clothing, household appliance anti-electromagnetic radiation masks, air filtration materials and other fields.

[0003] Regenerated cellulose fiber refers to a regenerated chemical fiber made from natural polymer cellulose (wood pulp, cotton linters, etc.) as raw materials through chemical methods, which is basically the same as the original polymer in chemical composition and has a cellulose structure of type II. However, when the bamboo charcoal particles are too large or the amount added to the cellulose solution is high, the bamboo charcoal will agglomerate in the slurry and cannot be stably dispersed, thereby affecting the spinnability of the bamboo charcoal fiber and the uniformity of the distribution of the bamboo charcoal in the fiber, and further affecting the mechanical properties and functionality of the bamboo charcoal fiber. Therefore, the amount of bamboo charcoal added in the market is generally less than 3%, and the bamboo charcoal fiber obtained with a low amount of bamboo charcoal addition has poor adsorption, antibacterial and antibacterial functions. Therefore, how to solve the problem of uniform and stable dispersion of bamboo charcoal in the polymer matrix and improve the interface interaction between the polymer and bamboo charcoal under high bamboo charcoal addition, and obtain high-performance and multifunctional bamboo charcoal fibers has become a difficulty and key.

[0004] Publication number is CN110158175B Chinese invention patent discloses bamboo charcoal slurry for viscose stock solution spinning and its preparation method, the method uses protein type surfactant and rosin-based hyperbranched surfactant with specific structure as dispersant together, utilizes the compounding between two surfactants to play synergistic effect, is conducive to the stable dispersion of bamboo charcoal powder in aqueous system. Publication number is CN100558952C Chinese invention patent discloses bamboo charcoal viscose fiber and its preparation method, the surfactant is dialkyl dimethyl ammonium chloride or polyalkyl trimethyl ammonium chloride, the dispersant is polysiloxane quaternary ammonium salt, dialkoxy silane quaternary ammonium salt or sodium tripolyphosphate. However, the method of improving the dispersion stability and particle size distribution of bamboo charcoal slurry by adding surfactant still cannot meet the continuous spinning requirements of viscose stock solution, and agglomeration and deposition are easy to occur in the spinning process, which brings problems such as poor spinnability and easy breakage of spinning to the spinning process, and uneven distribution and many defects in viscose fiber.

[0005] Organic functional modification of bamboo charcoal surface is another effective way to improve the dispersibility of bamboo charcoal in organic matrix, and it can also give bamboo charcoal more excellent properties. Patent CN115318260A provides a co-modification of manganese and cyclodextrin, which can improve the dispersibility of the material and increase the active sites of the material, greatly improving the adsorption and degradation performance, but the particle size of bamboo charcoal is too large to meet the particle size requirements of fiber spinning.

[0006] Therefore, it is of great significance to develop an efficient and environmentally friendly modification method to prepare functionalized bamboo charcoal, and to perform high-density modification to enhance the dispersibility and interfacial effect of bamboo charcoal materials in the regenerated cellulose matrix. Summary of the invention

[0007] The invention overcomes the shortcomings of the prior art and provides a method for preparing bamboo charcoal / regenerated cellulose composite fibers.

[0008] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing bamboo charcoal / regenerated cellulose composite fiber, comprising the following steps:

[0009] S1, crushing and sieving the bamboo charcoal, washing with water, and drying to obtain bamboo charcoal particles;

[0010] S2, dispersing bamboo charcoal in water, adding dopamine and tris(hydroxymethyl)aminomethane, adjusting the pH value, adding functional nanoparticles during stirring, and obtaining a polydopamine-modified bamboo charcoal dispersion;

[0011] S3, adding polysiloxane quaternary ammonium salt to the polydopamine modified bamboo charcoal dispersion, performing surface in-situ polymerization, centrifuging, washing and drying to obtain modified bamboo charcoal;

[0012] S4, mixing the modified bamboo charcoal, cellulose and an organic solvent to obtain a modified bamboo charcoal regenerated cellulose fiber spinning solution;

[0013] S5. The modified bamboo charcoal regenerated cellulose fiber spinning solution is wet-spun and then dried to obtain modified bamboo charcoal / regenerated cellulose composite fibers.

[0014] In a preferred embodiment of the present invention, in step S1, the preparation of the bamboo charcoal comprises the following steps:

[0015] S11, washing the bamboo material, and drying it at a temperature of 50 to 80° C. for 3 to 6 hours;

[0016] S12, treating the dried bamboo material in an oxygen-free atmosphere at a temperature of 230-300° C. for 1-2 h, raising the temperature to 450-600° C. for 2-4 h, and gradually cooling the carbonized bamboo charcoal from the highest calcination temperature to 50-60° C. to obtain a bamboo charcoal blank;

[0017] S13, cleaning the bamboo charcoal blank to neutrality, drying it at a temperature of 60 to 100° C. for 1 to 3 hours, and obtaining bamboo charcoal with a carbon-nitrogen ratio of 86.25 to 135.42.

[0018] In a preferred embodiment of the present invention, in step S1, the pulverization of the bamboo charcoal includes mechanical ball milling and air flow milling, and the grinding time is 2 to 8 hours; the particle size of the pulverized bamboo charcoal is 1 to 20 μm.

[0019] In a preferred embodiment of the present invention, in the step S2, the functional nanoparticles are one of silver nanoparticles or zinc oxide nanoparticles, and the particle size is 24 to 100 nm; the mass ratio of the bamboo charcoal, the dopamine, the tris(hydroxymethyl)aminomethane), the functional nanoparticles and the water is 1 to 3:0.25 to 2.4:0.25 to 3.5:0.5 to 1.5:100; the pH value is 7 to 9; and the stirring modification time is 2 to 6 hours.

[0020] In a preferred embodiment of the present invention, in the step S3, the polysiloxane quaternary ammonium salt is one of 3-(trimethoxysilyl)propyl hexadecyldimethylammonium chloride, 3-(trimethoxysilyl)propyl octadecyldimethylammonium chloride, 3-(triethoxysilyl)propyl hexadecyldimethylammonium chloride or 3-(triethoxysilyl)propyl octadecyldimethylammonium chloride.

[0021] In a preferred embodiment of the present invention, in the step S3, the mass ratio of the polysiloxane quaternary ammonium salt to the bamboo charcoal is 15 to 30:1; and the time of the surface in-situ polymerization is 4 to 8 hours.

[0022] In a preferred embodiment of the present invention, in the step S4, the mass ratio of the modified bamboo charcoal, the cellulose and the organic solvent is 0.1-0.3:3-8:85.

[0023] In a preferred embodiment of the present invention, in the step S4, the cellulose is one of bamboo pulp, cotton pulp, wood pulp or hemp pulp; the organic solvent is one of sodium sulfonate solution, tetrabutylammonium hydroxide / urea solution, alkali / urea solution, N-methylmorpholine-N-oxide solution or 1-allyl-3-methylimidazolium chloride ion liquid.

[0024] In a preferred embodiment of the present invention, in the step S5, before the wet spinning, the modified bamboo charcoal regenerated cellulose fiber spinning solution is centrifuged to remove bubbles.

[0025] In a preferred embodiment of the present invention, in the step S5, the modified bamboo charcoal / regenerated cellulose composite fiber is drawn twice, and the drawing multiple is 0.9 to 1.4.

[0026] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0027] (1) The present invention provides a method for preparing bamboo charcoal / regenerated cellulose composite fibers. The present invention adopts high-density modification of the surface of bamboo charcoal materials by polydopamine, which can significantly increase the density of active groups on the surface of bamboo charcoal particles, which is beneficial to improving the grafting efficiency of polysiloxane quaternary ammonium salt after secondary modification. At the same time, the modification effect is used to firmly combine with nanoparticles to increase the number of active sites on the surface of bamboo charcoal, so as to further improve the grafting efficiency of bamboo charcoal and polysiloxane quaternary ammonium salt, realize the interaction between functional bamboo charcoal filler and matrix and the dispersibility in the matrix, so that the prepared modified bamboo charcoal / regenerated cellulose composite fibers have excellent antibacterial properties and mechanical properties.

[0028] (2) In the present invention, polysiloxane quaternary ammonium salt modified bamboo charcoal is obtained by in-situ polymerization. The method is simple to operate, green and environmentally friendly. It not only enhances the hydrophilicity and antibacterial properties of bamboo charcoal, but also the long-chain structure of polysiloxane quaternary ammonium salt helps to improve the dispersibility of bamboo charcoal in the regenerated cellulose matrix, thereby also having a certain impact on the mechanical properties of the fiber. Because the polysiloxane quaternary ammonium salt molecule contains quaternary ammonium groups, the polydopamine layer formed by dopamine on the surface of bamboo charcoal has good adhesion and reactivity. When the polysiloxane quaternary ammonium salt is grafted to the surface of bamboo charcoal through chemical bonds, the quaternary ammonium groups therein are firmly fixed on the bamboo charcoal particles and dispersed into the regenerated cellulose fibers along with the bamboo charcoal particles, thereby effectively improving the antibacterial properties of the fibers. At the same time, the functional groups in the polysiloxane quaternary ammonium salt molecules can form hydrogen bonds or ionic bonds with groups such as hydroxyl groups on the surface of bamboo charcoal and regenerated cellulose fibers, thereby not only enhancing the compatibility between bamboo charcoal and regenerated cellulose, but also improving the interfacial bonding force between them, thereby better improving the mechanical properties of the fibers.

[0029] (3) In the present invention, the functional nanoparticles are used to give the composite fiber additional antibacterial and mechanical properties. The difference between the positive charge on the surface of the functional nanoparticles and the negative charge on the bacterial cell wall enables the nanoparticles to be strongly adsorbed on the bacterial surface and destroy the integrity of the bacterial cell membrane through electrostatic interaction. At the same time, the active sites on the surface of the nanoparticles can react with the biological molecules inside the bacteria to further inhibit or kill the bacteria. The functional nanoparticles have a large specific surface area and rich surface chemical properties, which enable the nanoparticles to form a strong interaction with the active sites on the surface of bamboo charcoal, increase the number of active sites on the surface of bamboo charcoal, and provide more grafting sites for polysiloxane quaternary ammonium salts, thereby improving the grafting efficiency and further improving the antibacterial and mechanical properties.

[0030] (4) In the present invention, bamboo charcoal with a high carbon-nitrogen ratio has more micropores, specific surface area and unsaturated bonds, which helps to deposit polydopamine on the surface of bamboo charcoal more evenly, thereby increasing the available space of surface active groups. In addition, the bamboo charcoal with a high carbon-nitrogen ratio has more carbon-based active sites on the surface, which can serve as the catalytic center of the polymerization reaction of polydopamine, so that the carbon atoms in the bamboo charcoal can form stronger chemical bonds with the nitrogen atoms in the polydopamine, which can make the interaction between the bamboo charcoal and the polydopamine stronger, thereby enhancing the interfacial bonding force between the bamboo charcoal and the polydopamine, thereby helping to improve the grafting effect and further improve its antibacterial and mechanical properties.

[0031] (5) In the present invention, by providing an alkaline modification environment, functional groups such as amino groups and catechol groups in dopamine molecules are more easily deprotonated to form negatively charged ions, which can undergo electrostatic interactions and hydrogen bonding, thereby promoting the self-polymerization ability of dopamine, enabling it to be applied to the surface modification of functional nanoparticles, helping to stabilize the charge on the surface of the nanoparticles, and significantly improving their stability and dispersibility in aqueous solutions, preventing agglomeration, thereby achieving a synergistic effect of dopamine, functional nanoparticles and polysiloxane quaternary ammonium salts, and effectively improving the antibacterial effect and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 1 is a microscopic morphology of the surface of bamboo charcoal fiber prepared in Example 1 (a) and Example 2 (b) of the present invention;

[0034] Figure 2 The microscopic morphology of the cross section of the bamboo charcoal fiber prepared in Example 1 (a), (b) and Example 2 (c), (d) of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0037] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained through the preparation methods of existing technologies.

[0038] A method for preparing bamboo charcoal / regenerated cellulose composite fiber comprises the following steps:

[0039] S1, crushing and sieving the bamboo charcoal, washing with water, and drying to obtain bamboo charcoal particles;

[0040] S2, dispersing bamboo charcoal in water, adding dopamine and tris(hydroxymethyl)aminomethane, adjusting the pH value, adding functional nanoparticles during stirring, and obtaining a polydopamine-modified bamboo charcoal dispersion;

[0041] S3, adding polysiloxane quaternary ammonium salt to the polydopamine modified bamboo charcoal dispersion, performing surface in-situ polymerization, centrifuging, washing and drying to obtain modified bamboo charcoal;

[0042] S4, mixing the modified bamboo charcoal, cellulose and an organic solvent to obtain a modified bamboo charcoal regenerated cellulose fiber spinning solution;

[0043] S5. The modified bamboo charcoal regenerated cellulose fiber spinning solution is wet-spun and then dried to obtain modified bamboo charcoal / regenerated cellulose composite fibers.

[0044] The commonly used dispersion methods in the art are applicable to the present invention. In one embodiment of the present invention, the dispersion method is to mix the bamboo charcoal and the solution with magnetic stirring, and then perform ultrasound at room temperature for 10 to 60 minutes.

[0045] In some specific embodiments, in step S1, the preparation of bamboo charcoal comprises the following steps:

[0046] S11, washing the bamboo material, and drying it at a temperature of 50 to 80° C. for 3 to 6 hours;

[0047] S12, treating the dried bamboo material in an oxygen-free atmosphere at a temperature of 230-300° C. for 1-2 h, raising the temperature to 450-600° C. for 2-4 h, and gradually cooling the carbonized bamboo charcoal from the highest calcination temperature to 50-60° C. to obtain a bamboo charcoal blank;

[0048] S13, cleaning the bamboo charcoal blank to neutrality, drying it at a temperature of 60 to 100° C. for 1 to 3 hours, and obtaining bamboo charcoal with a carbon-nitrogen ratio of 86.25 to 135.42.

[0049] It should be noted that in step S11, bamboo materials are bamboo materials from Dong'an, Hunan Province as raw materials.

[0050] In some specific embodiments, in step S1, the pulverization of the bamboo charcoal includes mechanical ball milling and air flow milling, and the grinding time is 2 to 8 hours; the particle size of the pulverized bamboo charcoal is 1 to 20 μm.

[0051] In some specific embodiments, in step S2, the functional nanoparticles are one of silver nanoparticles or zinc oxide nanoparticles, with a particle size of 24 to 100 nm; the mass ratio of bamboo charcoal, dopamine, tris(hydroxymethyl)aminomethane, functional nanoparticles and water is 1 to 3: 0.25 to 2.4: 0.25 to 3.5: 0.5 to 1.5: 100; the pH value is 7 to 9; and the stirring modification time is 2 to 6 hours.

[0052] In some specific embodiments, in step S3, the polysiloxane quaternary ammonium salt is one of 3-(trimethoxysilyl)propyl hexadecyldimethylammonium chloride, 3-(trimethoxysilyl)propyl octadecyldimethylammonium chloride, 3-(triethoxysilyl)propyl hexadecyldimethylammonium chloride or 3-(triethoxysilyl)propyl octadecyldimethylammonium chloride; the mass ratio of the polysiloxane quaternary ammonium salt to the bamboo charcoal is 15 to 30:1; and the time for surface in situ polymerization is 4 to 8 hours.

[0053] In some specific embodiments, in step S4, the mass ratio of modified bamboo charcoal, cellulose and organic solvent is 0.1-0.3:3-8:85; cellulose is one of bamboo pulp, cotton pulp, wood pulp or hemp pulp; and the organic solvent is one of sodium sulfonate solution, tetrabutylammonium hydroxide / urea solution, alkali / urea solution, N-methylmorpholine-N-oxide solution or 1-allyl-3-methylimidazolium chloride ion liquid.

[0054] In some specific embodiments, in step S5, before wet spinning, the modified bamboo charcoal regenerated cellulose fiber spinning solution is centrifuged to remove bubbles; the modified bamboo charcoal / regenerated cellulose composite fiber is subjected to two drafting steps, and the drafting multiple is 0.9 to 1.4.

[0055] Example 1

[0056] A method for preparing bamboo charcoal / regenerated cellulose composite fiber comprises the following steps:

[0057] S1. Wash the bamboo and dry it at 60°C for 4 hours;

[0058] S2, treating the dried bamboo material in a nitrogen atmosphere at a temperature of 260° C. for 1.5 h, heating to 520° C., treating for 2 h to complete carbonization, and gradually cooling the carbonized bamboo charcoal from 520° C. to 50° C. to obtain a bamboo charcoal blank;

[0059] S3, washing the bamboo charcoal blank to neutrality, drying it at 80°C for 2h, and obtaining bamboo charcoal with a carbon-nitrogen ratio of 92.18;

[0060] S4, putting bamboo charcoal with a carbon-nitrogen ratio of 92.18 into a high-energy ball mill for 5 hours, and the particle size after grinding is 2 μm, taking 10 g of the refined bamboo charcoal powder and mixing it with 1000 ml of water, centrifuging and washing it at a speed of 4000 r / min for 2 cycles, and drying the washed bamboo charcoal in a drying oven to obtain bamboo charcoal particles;

[0061] S5, dispersing 2 g of bamboo charcoal in 100 ml of water, stirring for 5 min, using ultrasonic oscillation for 10 min, adding 1 g of dopamine for magnetic stirring, and adding 1.3 g of tris(hydroxymethyl)aminomethane buffer, adjusting the pH value of the mixed solution to 8.5, stirring for 4 h, and adding 0.5 g of silver nanoparticles with a particle size of 24 nm during stirring to obtain a polydopamine-modified bamboo charcoal dispersion;

[0062] S6, adding 25 ml of 3-(trimethoxysilyl)propyl hexadecyldimethylammonium chloride to the polydopamine modified bamboo charcoal dispersion, stirring for 5 hours, centrifuging and washing at a speed of 4000 r / min, washing with water to remove organic monomers, and vacuum drying at a temperature of 60° C. to obtain modified bamboo charcoal;

[0063] S7, adding 1.1g of modified bamboo charcoal to 220g of urea / tetrabutylammonium hydroxide mixed solvent (mass ratio is 2:5, tetrabutylammonium hydroxide solution is a 40% aqueous solution), stirring to make the solvent evenly dispersed, adding 12.5g of crushed bamboo pulp to the above mixed solvent and stirring to dissolve, to obtain modified bamboo charcoal regenerated cellulose fiber spinning solution;

[0064] S8. Centrifuge the modified bamboo charcoal regenerated cellulose fiber spinning solution to remove bubbles, carry out wet spinning, and pass through a coagulation bath, a first drafting roller, a water washing bath, a second drafting roller, and a drying box in sequence to obtain modified bamboo charcoal / regenerated cellulose composite fibers; the coagulation bath is a mixed solution of citric acid, sodium citrate, ethylene glycol and water in a mass ratio of 14:5:80:110, the coagulation bath temperature is 25°C, the cleaning tank solution is water, the first drafting multiple is 1.1, the second drafting multiple is 1.0, and the drying temperature is 80°C.

[0065] Example 2

[0066] A method for preparing bamboo charcoal / regenerated cellulose composite fiber comprises the following steps:

[0067] S1. Wash the bamboo and dry it at 60°C for 4 hours;

[0068] S2, treating the dried bamboo material in a nitrogen atmosphere at a temperature of 260° C. for 1.5 h, heating to 520° C., treating for 2 h to complete carbonization, and gradually cooling the carbonized bamboo charcoal from 520° C. to 50° C. to obtain a bamboo charcoal blank;

[0069] S3, washing the bamboo charcoal blank to neutrality, drying it at 80°C for 2h, and obtaining bamboo charcoal with a carbon-nitrogen ratio of 92.18;

[0070] S4, putting bamboo charcoal with a carbon-nitrogen ratio of 92.18 into a high-energy ball mill for 5 hours, and the particle size after grinding is 2 μm, taking 10 g of the refined bamboo charcoal powder and mixing it with 1000 ml of water, centrifuging and washing it at a speed of 4000 r / min for 2 cycles, and drying the washed bamboo charcoal in a drying oven to obtain bamboo charcoal particles;

[0071] S5, dispersing 2 g of bamboo charcoal in 100 ml of water, stirring for 5 min, using ultrasonic oscillation for 10 min, adding 1 g of dopamine for magnetic stirring, and adding 1.3 g of tris(hydroxymethyl)aminomethane buffer, adjusting the pH value of the mixed solution to 8.5, stirring for 4 h, and adding 0.5 g of zinc oxide nanoparticles with a particle size of 24 nm during stirring to obtain a polydopamine-modified bamboo charcoal dispersion;

[0072] S6, adding 25 ml of 3-(trimethoxysilyl)propyl hexadecyldimethylammonium chloride to the polydopamine modified bamboo charcoal dispersion, stirring for 5 hours, centrifuging and washing at a speed of 4000 r / min, washing with water to remove organic monomers, and vacuum drying at a temperature of 60° C. to obtain modified bamboo charcoal;

[0073] S7, adding 1.1 g of modified bamboo charcoal to a mixed solvent of 240 g of NaOH / urea / water (mass ratio is 7:12:81), stirring to make the solvent evenly dispersed, adding 12 g of crushed bamboo pulp to the mixed solvent and stirring to dissolve, to obtain a modified bamboo charcoal regenerated cellulose fiber spinning solution;

[0074] S8. After vacuum degassing the modified bamboo charcoal regenerated cellulose fiber spinning solution, dry-wet spinning is carried out, and the fibers are passed through an air layer, a coagulation bath, a first drafting roller, a water washing bath, a second drafting roller, and a drying box in sequence to obtain modified bamboo charcoal / regenerated cellulose composite fibers; the air layer height is 10 mm, the coagulation bath is a mixed solution of citric acid, sodium citrate, ethylene glycol and water, with a mass ratio of 14:5:80:110, the coagulation bath temperature is 25°C, the cleaning tank solution is water, the first drafting multiple is 1.2, the second drafting multiple is 1.0, and the drying temperature is 80°C.

[0075] In order to verify the successful acquisition of the modified bamboo charcoal / regenerated cellulose composite fibers in Examples 1 and 2, Figure 1(a) shows the surface microscopic morphology of the bamboo charcoal fiber prepared in Example 1 of the present invention, Figure 1 (b) shows the surface microscopic morphology of the bamboo charcoal fiber prepared in Example 2 of the present invention; Figure 2 (a) and (b) are microscopic morphology images of the transverse cross section and vertical cross section of the bamboo charcoal fiber prepared in Example 1 of the present invention, respectively. Figure 2 (c) and (d) respectively show the transverse cross-section and vertical cross-section microscopic morphology of the bamboo charcoal fiber prepared in Example 2 of the present invention; the modified bamboo charcoal / regenerated cellulose composite fiber of the present invention has a large specific surface area and pore volume, and contains a large number of micropores and mesopores. The prepared modified bamboo charcoal regenerated cellulose fiber has excellent adsorption properties.

[0076] Example 3

[0077] This embodiment is basically the same as embodiment 1, except that: step S1 is: washing the bamboo material, and drying it at a temperature of 80°C for 3 hours; step S3 is: washing the bamboo charcoal blank to neutrality, and drying it at a temperature of 80°C for 3 hours to obtain bamboo charcoal with a carbon-nitrogen ratio of 98.34.

[0078] Example 4

[0079] This embodiment is basically the same as Embodiment 1, except that: Step S2 is as follows: the dried bamboo material is treated in a nitrogen atmosphere at a temperature of 300°C for 2 hours, the temperature is raised to 600°C, and the treatment is performed for 3 hours to complete carbonization; the carbonized bamboo charcoal is gradually cooled from 600°C to 60°C to obtain a bamboo charcoal blank; and finally, bamboo charcoal with a carbon-nitrogen ratio of 135.42 is obtained.

[0080] Example 5

[0081] This embodiment is basically the same as Embodiment 1, except that: Step S2 is as follows: the dried bamboo material is treated in a nitrogen atmosphere at a temperature of 230°C for 1 hour, the temperature is raised to 450°C, and the treatment is performed for 3 hours to complete carbonization; the carbonized bamboo charcoal is gradually cooled from 450°C to 50°C to obtain a bamboo charcoal blank; and finally, bamboo charcoal with a carbon-nitrogen ratio of 86.25 is obtained.

[0082] Comparative Example 1

[0083] This comparative example is basically the same as Example 1, except that there is no bamboo charcoal, and the preparation comprises the following steps: adding 12.5 g of crushed bamboo pulp to 220 g of urea / tetrabutylammonium hydroxide mixed solvent (mass ratio is 2:5, and the tetrabutylammonium hydroxide solution is a 40% aqueous solution), stirring and dissolving to obtain a spinning solution; centrifuging the spinning solution to remove bubbles, wet spinning, and sequentially passing through a coagulation bath, a first drafting roller, a water washing bath, a second drafting roller, and a drying box to obtain fibers; the coagulation bath is a mixed solution of citric acid, sodium citrate, ethylene glycol and water, with a mass ratio of 14:5:80:110, the coagulation bath temperature is 25°C, the cleaning tank solution is water, the first drafting multiple is 1.1, the second drafting multiple is 1.0, and the drying temperature is 80°C.

[0084] Comparative Example 2

[0085] This comparative example is basically the same as Example 1, except that: there are no steps S5 and S6, and step S7 is: adding 1.1 g of bamboo charcoal particles to 220 g of urea / tetrabutylammonium hydroxide mixed solvent (mass ratio is 2:5, tetrabutylammonium hydroxide solution is a 40% aqueous solution), stirring to evenly disperse the solvent, adding 12.5 g of crushed bamboo pulp to the above mixed solvent and stirring to dissolve, to obtain bamboo charcoal regenerated cellulose fiber spinning solution.

[0086] Comparative Example 3

[0087] This comparative example is basically the same as Example 1, except that: Step S6 is: centrifugally washing the polydopamine modified bamboo charcoal dispersion at a speed of 4000 r / min, washing with water to remove organic monomers, and vacuum drying at a temperature of 60° C. to obtain modified bamboo charcoal.

[0088] Comparative Example 4

[0089] This comparative example is basically the same as Example 1, except that: Step S5 is: dispersing 2 g of bamboo charcoal in 100 ml of water, stirring for 5 min, using ultrasonic oscillation for 10 min, adding 1 g of dopamine for magnetic stirring, and adding 1.3 g of tris(hydroxymethyl)aminomethane buffer solution, adjusting the pH value of the mixed solution to 8.5, stirring for 4 h, and obtaining a polydopamine-modified bamboo charcoal dispersion.

[0090] Comparative Example 5

[0091] This comparative example is basically the same as Example 1, except that: there are no steps S1, S2 and S3, and the step S4 is: put commercially available bamboo charcoal with a carbon-nitrogen ratio of 23.63 into a high-energy ball mill for ball milling for 5 hours, and the particle size after grinding is 2 μm, take 10 g of the refined bamboo charcoal powder and mix it with 1000 ml of water, centrifuge and wash it at a speed of 4000 r / min for 2 cycles, and dry the washed bamboo charcoal in a drying oven to obtain bamboo charcoal particles.

[0092] Comparative Example 6

[0093] This comparative example is basically the same as Example 1, except that: there are no steps S1, S2 and S3, and the step S4 is: put commercially available bamboo charcoal with a carbon-nitrogen ratio of 158.93 into a high-energy ball mill for ball milling for 5 hours, and the particle size after grinding is 2 μm, take 10 g of the refined bamboo charcoal powder and mix it with 1000 ml of water, centrifuge and wash it at a speed of 4000 r / min for 2 cycles, and dry the washed bamboo charcoal in a drying oven to obtain bamboo charcoal particles.

[0094] Comparative Example 7

[0095] This comparative example is substantially the same as Example 1, except that in step S5, the pH value of the mixed solution is adjusted to 5.8.

[0096] Comparative Example 8

[0097] This comparative example is substantially the same as Example 1, except that in step S5, the pH value of the mixed solution is adjusted to 10.

[0098] Performance testing: The fibers obtained in the above Examples 1-5 and Comparative Examples 1-8 were tested for antibacterial properties, elongation at break and breaking strength in turn.

[0099] Antibacterial property: Place 3mm round antibacterial test fiber on the bacterial culture dish, culture it for 12 hours, and observe and measure its prevention and control effect.

[0100] Elongation at break and breaking strength: Tested in accordance with GB / T 14337-2008 “Chemical fibers: Test method for tensile properties of staple fibers”.

[0101] The performance test results of antibacterial property, elongation at break and breaking strength of Examples 1-5 and Comparative Examples 1-8 are shown in Table 1.

[0102] Table 1:

[0103]

[0104]

[0105] It can be seen from the test results in Table 1 that by comparing Example 1 with Comparative Example 1 and Comparative Example 2, it can be learned that, compared with the unmodified bamboo charcoal and the unadded bamboo charcoal, the high-density modification of the bamboo charcoal material surface by polydopamine in Example 1 of the present invention can significantly increase the density of the active groups on the surface of the bamboo charcoal particles, which is beneficial to improve the grafting efficiency of the polysiloxane quaternary ammonium salt after the secondary modification. At the same time, the modification effect is firmly combined with the nanoparticles to increase the number of active sites on the surface of the bamboo charcoal, so as to further improve the grafting efficiency of the bamboo charcoal and the polysiloxane quaternary ammonium salt, realize the interaction between the functional bamboo charcoal filler and the matrix and the dispersibility in the matrix, so that the prepared modified bamboo charcoal / regenerated cellulose composite fiber has excellent antibacterial properties and mechanical properties.

[0106] By comparing Example 1 with Example 3, it can be seen that in the preparation of bamboo charcoal, the pretreatment of bamboo drying and the post-treatment of bamboo charcoal blank cleaning and drying have little effect on the carbon-nitrogen ratio of the prepared bamboo charcoal. It is mainly the removal of moisture and cleaning that affect the moisture content and cleanliness of the bamboo, and have little direct effect on the carbon-nitrogen ratio. By comparing Example 1 with Example 4 and Example 5, it can be seen that as the carbonization temperature increases, the organic matter in the bamboo will undergo more intense pyrolysis and polycondensation reactions, which can promote the release of non-carbon elements in the form of gas, thereby increasing the carbon content in the bamboo charcoal. Reduce the nitrogen content and thus increase the carbon-nitrogen ratio. On the contrary, a lower carbonization temperature will slow down the rate of pyrolysis and polycondensation reactions, allowing more nitrogen elements to remain in the bamboo charcoal, thereby reducing the carbon-nitrogen ratio. At the same time, extending the carbonization time can make the pyrolysis and polycondensation reactions more complete, which is beneficial to the further release of non-carbon elements. The shorter carbonization time is not enough to effectively release all non-carbon elements, which can easily lead to a relatively high nitrogen content in the bamboo charcoal and a low carbon-nitrogen ratio. The carbon-nitrogen ratio of the bamboo charcoal can be effectively regulated by changing the temperature and processing time during pre-carbonization and carbonization.

[0107] By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the bamboo charcoal with a high carbon-nitrogen ratio has more micropores, specific surface area and unsaturated bonds, which helps the deposition of polydopamine on the surface of the bamboo charcoal to be more uniform, thereby increasing the available space of the surface active groups, and the bamboo charcoal with a high carbon-nitrogen ratio has more carbon-based active sites on the surface, which can serve as the catalytic center of the polymerization reaction of polydopamine, so that the carbon atoms in the bamboo charcoal can form stronger chemical bonds with the nitrogen atoms in the polydopamine, which can make the interaction between the bamboo charcoal and the polydopamine stronger, thereby enhancing the interfacial bonding force between the bamboo charcoal and the polydopamine, and thus helping Improve the grafting effect, further improve its antibacterial and mechanical properties. At the same time, bamboo charcoal with too low or too high carbon-nitrogen ratio will have a certain impact on the subsequent modification and grafting effect, which will further affect the antibacterial and mechanical properties. Because bamboo charcoal with too low carbon-nitrogen ratio has fewer surface active sites and more defects or vacancies in the carbon skeleton, the bamboo charcoal is easily damaged during the modification and grafting process, resulting in a decrease in performance. Too high a carbon-nitrogen ratio will also destroy the carbon skeleton structure of bamboo charcoal, and affect the attachment and distribution of the modified and grafted molecules on the surface of bamboo charcoal, thereby resulting in a decrease in mechanical properties and affecting its antibacterial properties.

[0108] By comparing Example 1 with Comparative Example 5, it can be seen that the polysiloxane quaternary ammonium salt during secondary modification not only enhances the hydrophilicity and antibacterial properties of bamboo charcoal, but the long-chain structure of the polysiloxane quaternary ammonium salt also helps to improve the dispersibility of bamboo charcoal in the regenerated cellulose matrix, thereby also having a certain impact on the mechanical properties of the fiber. Because the polysiloxane quaternary ammonium salt molecule contains a quaternary ammonium group, the polydopamine layer formed by dopamine on the surface of the bamboo charcoal has good adhesion and reactivity. When the polysiloxane quaternary ammonium salt is grafted to the surface of the bamboo charcoal through chemical bonds, the quaternary ammonium group therein is firmly fixed on the bamboo charcoal particles and dispersed into the regenerated cellulose fibers along with the bamboo charcoal particles, effectively improving the antibacterial properties of the fibers. At the same time, the functional groups in the polysiloxane quaternary ammonium salt molecules can form hydrogen bonds or ionic bonds with groups such as hydroxyl groups on the surface of the bamboo charcoal and the regenerated cellulose fibers, which not only enhances the compatibility between the bamboo charcoal and the regenerated cellulose, but also improves the interfacial bonding force between them, thereby better improving the mechanical properties of the fibers.

[0109] By comparing Example 1 and Example 2 with Comparative Example 6, it can be seen that the functional nanoparticles impart additional antibacterial and mechanical properties to the composite fiber. This is because the difference between the positive charge on the surface of the functional nanoparticles and the negative charge on the bacterial cell wall enables the nanoparticles to be strongly adsorbed on the bacterial surface and destroy the integrity of the bacterial cell membrane through electrostatic interactions. At the same time, the active sites on the surface of the nanoparticles can react with the biological molecules inside the bacteria to further inhibit or kill the bacteria. The functional nanoparticles have a large specific surface area and rich surface chemical properties, which enable the nanoparticles to form a strong interaction with the active sites on the surface of bamboo charcoal, increase the number of active sites on the surface of bamboo charcoal, and provide more grafting sites for polysiloxane quaternary ammonium salts, thereby improving the grafting efficiency and further improving the antibacterial and mechanical properties.

[0110] By comparing Example 1 with Comparative Example 7, it can be seen that in an acidic environment, the self-polymerization process of dopamine is inhibited, resulting in the formation of polydopamine being blocked, so that the antibacterial agent on the surface of the nanoparticles cannot be effectively fixed or is unevenly distributed, and the functional nanoparticles are easily dissolved and structurally destroyed in an acidic environment, thereby reducing the overall antibacterial performance and causing a decrease in mechanical properties. In an alkaline environment, functional groups such as amino groups and catechol groups in dopamine molecules are more likely to be deprotonated to form negatively charged ions, which can undergo electrostatic interactions and hydrogen bonding, promoting the self-polymerization ability of dopamine, making it The invention can be applied to the surface modification of functional nanoparticles, which is helpful to stabilize the charge on the surface of the nanoparticles, can significantly improve the stability and dispersibility of the nanoparticles in aqueous solution, and prevent agglomeration, thereby achieving the synergistic effect of dopamine, functional nanoparticles and polysiloxane quaternary ammonium salts, and effectively improving the antibacterial effect and mechanical properties. By comparing Example 1 with Comparative Example 8, it can be seen that although the alkaline environment is conducive to the self-polymerization of dopamine and the fixation of the antibacterial agent, an excessively high alkaline environment is prone to cause the antibacterial agent to undergo hydrolysis or decomposition reaction, and at the same time affects the stability of the polysiloxane quaternary ammonium salt, thereby reducing the antibacterial activity and reducing its mechanical properties.

[0111] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0112] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing bamboo charcoal / regenerated cellulose composite fiber, characterized in that: The following steps are involved: S1, crushing and sieving the bamboo charcoal, washing with water, and drying to obtain bamboo charcoal particles; S2, dispersing bamboo charcoal in water, adding dopamine and tris(hydroxymethyl)aminomethane, adjusting the pH value, adding functional nanoparticles during stirring, and obtaining a polydopamine-modified bamboo charcoal dispersion; S3, adding polysiloxane quaternary ammonium salt to the polydopamine modified bamboo charcoal dispersion, performing surface in-situ polymerization, centrifuging, washing and drying to obtain modified bamboo charcoal; S4, mixing the modified bamboo charcoal, cellulose and an organic solvent to obtain a modified bamboo charcoal regenerated cellulose fiber spinning solution; S5. The modified bamboo charcoal regenerated cellulose fiber spinning solution is wet-spun and then dried to obtain modified bamboo charcoal / regenerated cellulose composite fibers.

2. The method for preparing a bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In step S1, the preparation of the bamboo charcoal comprises the following steps: S11, washing the bamboo material, and drying it at a temperature of 50 to 80° C. for 3 to 6 hours; S12, treating the dried bamboo material in an oxygen-free atmosphere at a temperature of 230-300° C. for 1-2 h, raising the temperature to 450-600° C. for 2-4 h, and gradually cooling the carbonized bamboo charcoal from the highest calcination temperature to 50-60° C. to obtain a bamboo charcoal blank; S13, cleaning the bamboo charcoal blank to neutrality, drying it at a temperature of 60 to 100° C. for 1 to 3 hours, and obtaining bamboo charcoal with a carbon-nitrogen ratio of 86.25 to 135.

42.

3. The method for preparing a bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S1, the pulverization of the bamboo charcoal includes mechanical ball milling and air flow milling, and the grinding time is 2 to 8 hours; the particle size of the pulverized bamboo charcoal is 1 to 20 μm.

4. The method for preparing a bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S2, the functional nanoparticles are one of silver nanoparticles or zinc oxide nanoparticles, and the particle size is 24 to 100 nm; the mass ratio of the bamboo charcoal, the dopamine, the tris(hydroxymethyl)aminomethane), the functional nanoparticles and the water is 1 to 3: 0.25 to 2.4: 0.25 to 3.5: 0.5 to 1.5: 100; the pH value is 7 to 9; and the stirring modification time is 2 to 6 hours.

5. The method for preparing a bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S3, the polysiloxane quaternary ammonium salt is one of 3-(trimethoxysilyl)propyl hexadecyldimethylammonium chloride, 3-(trimethoxysilyl)propyl octadecyldimethylammonium chloride, 3-(triethoxysilyl)propyl hexadecyldimethylammonium chloride or 3-(triethoxysilyl)propyl octadecyldimethylammonium chloride.

6. The method for preparing a bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S3, the mass ratio of the polysiloxane quaternary ammonium salt to the bamboo charcoal is 15 to 30:1; and the time of the surface in-situ polymerization is 4 to 8 hours.

7. The method for preparing bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S4, the mass ratio of the modified bamboo charcoal, the cellulose and the organic solvent is 0.1-0.3:3-8:

85.

8. The method for preparing bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In step S4, the cellulose is one of bamboo pulp, cotton pulp, wood pulp or hemp pulp; the organic solvent is one of sodium sulfonate solution, tetrabutylammonium hydroxide / urea solution, alkali / urea solution, N-methylmorpholine-N-oxide solution or 1-allyl-3-methylimidazolium chloride ion liquid.

9. The method for preparing bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S5, before the wet spinning, the modified bamboo charcoal regenerated cellulose fiber spinning solution is centrifuged to remove bubbles.

10. The method for preparing bamboo charcoal / regenerated cellulose composite fiber according to claim 1, characterized in that: In the step S5, the modified bamboo charcoal / regenerated cellulose composite fiber is drawn twice, and the drawing multiple is 0.9 to 1.4.

Citation Information

Patent Citations

  • Bamboo-carbon viscose fibre and its production method

    CN100558952C

  • Bamboo charcoal slurry for viscose spinning and its preparation method

    CN110158175B

  • Manganese and cyclodextrin co-modified bamboo charcoal material as well as preparation method and application thereof

    CN115318260A

  • Bamboo-carbon viscose fibre and its production

    CN101029420A

  • Preparation method of nano-antibacterial bamboo carbon fiber

    CN104532379A